My Wage is Unfair! Just a Feeling or Comparison with Peers? - Stefan Schneck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper descriptively analyzes the nexus between income comparisons and perceptions of unfair pay. A German household survey reveals that individuals who perceive their wages as unfair earn significantly lower wages than fairly paid individuals with similar characteristics. This suggests that unfairness perceptions with respect to wages are based on sound income comparisons with peers. When asked about a subjectively fair amount in Euros, individuals tend to claim much higher wages than fairly paid individuals with identical characteristics.
More recent version: http://hdl.handle.net/10419/83519
Keywords: J30; J31; 330; Fairness; Wages; Gerechtigkeit; Lohn